2022
DOI: 10.3389/fphar.2022.828094
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring of Anti-Thymocyte Globulin in Allogeneic Stem Cell Transplantation: Proof of Concept

Abstract: Anti-thymocyte globulin (ATG), a polyclonal antibody, is used in allogeneic hematopoietic cell transplantation (HCT) to prevent graft-vs.-host-disease (GvHD) and graft failure (GF). Overexposure to ATG leads to poor early T-cell recovery, which is associated with viral infections and poor survival. Patients with severe inflammation are at high risk for GF and GvHD, and may have active infections warranting swift T-cell recovery. As ATG exposure may be critical in these patients, individualized dosing combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Second, likely reflecting the disparities in the studied HCT settings, our dosing regimen is a function of IBW alone, whereas the Admiraal's was of ALC and total body weight 14,15 . Lastly, Admiraal et al performed their PKPD study based on active fraction of rATG measured by quantitative flow cytometry, 21 while we used ELISA to measure total rATG including both active and inactive fractions. Subsequently, the findings generated by these two distinct bioassay methods may not be translatable to each other.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, likely reflecting the disparities in the studied HCT settings, our dosing regimen is a function of IBW alone, whereas the Admiraal's was of ALC and total body weight 14,15 . Lastly, Admiraal et al performed their PKPD study based on active fraction of rATG measured by quantitative flow cytometry, 21 while we used ELISA to measure total rATG including both active and inactive fractions. Subsequently, the findings generated by these two distinct bioassay methods may not be translatable to each other.…”
Section: Discussionmentioning
confidence: 99%
“…The steps 1–4 describe the probabilities of an event over the index period without accounting for censoring events; and thus, the results for the outcomes up to day +100 are statistically correct (no censoring) while those up to day +730 should be interpreted as approximation (censored 10 of 103 patients). Of note, the difference in PK assays precluded evaluation of previously identified thresholds by Admiraal et al, 14,15 where only the active fraction of ATG (“arbitrary unit/mL”) was measured by quantitative flow cytometry, while total ATG (μg/mL) was measured using ELISA in the present study 19,21 We evaluated the following three exposure variables of interest based on the previous reports: area‐under‐the‐curve of rATG concentration–time from the start of first infusion to day 0 (AUC pre‐day_0 ), C day_0 , and AUC post day 0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacokinetic studies have demonstrated wide variations among pediatric patients with slow clearance resulting in delayed immune reconstitution, increased risk of infections and transplant-related mortality, or fast clearance resulting in more GvHD (8,9,10). Using a validated pharmacokinetic model, Admiraal et al concluded that a xed 10 mg/kg dose resulted in excessive exposure for children with higher body weight and low lymphocyte count, setting the stage for individualized dosing based on these two parameters (11,12). Children's body weight varies widely with age, and lymphocyte counts can vary from < 100/µL in patients with acute leukemia and severe combined immune de ciencies to normal levels (> 2500 /µL) in congenital anemias and inborn errors of metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In hematology, ATG from horses has been found to be superior to ATG from rabbits in treatment of aplastic anaemia [4]. Individualized dosing combined with therapeutic drug monitoring is recommended to improve outcomes of transplant cases [5]. A cost-effective approach is suggested in prescribing ATG; it should be balanced with not only efficacy but also safety [6][7][8].…”
Section: Introductionmentioning
confidence: 99%